MSME SUCCESS IS REVIEWED FROM CREATIVITY AND SOCIAL MEDIA USERS - Napitupulu, Enjel Lina Yanti; Ni Bulan, Tapi Rondang; Setiawan, Teguh (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This research aims to analyze how creativity and social media users influence the success of MSMEs. The population in this study was 125 MSMEs and all of them were sampled in this study using saturated sampling techniques. The analysis technique used is multiple linear regression. The research results show that creativity has a positive and significant effect on the success of MSMEs with a value of (5.394 > 1.979) and a Sig. (0.000 < 0.05). Social media users have a positive and significant influence on the success of MSMEs with a value of (3.801 > 1.979) and a Sig value. (0.000 < 0.05). Simultaneously shows that creativity and social media users have a significant influence on the success of MSMEs in Kel. Harjosari I, Kec. Medan Amplas with Fcount > Ftable value (18.068 > 3.070) or sig F < 5% (0.000 < 0.05).